2020
DOI: 10.1186/s13568-020-01074-8
|View full text |Cite
|
Sign up to set email alerts
|

Mukonal exerts anticancer effects on the human breast cancer cells by inducing autophagy and apoptosis and inhibits the tumor growth in vivo

Abstract: Mukonal is an active member of carbazole alkaloids isolated from Murraya koenigii. It has been shown to possess remarkable biological and pharmacological activities including anticancer activity. Therefore, the aim of current investigation was to explore anti-breast cancer activity of mukonal and to explore the underlying mechanism. Results indicate that mukonal has potential to induce antiproliferative effects against MDA-MB-231 and SK-BR-3 cells with an IC 50 of 7.5 µM. No significant toxicity of mukonal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…and Pellina sp. p62/SQSTM1, LC3-II↑ Inhibit autophagy AsPC-1 and PANC-1 Pancreatic cancer [ 216 ] Indole-3-carbinol Cruciferous vegetables p62↓ LC3-II↑ Induce autophagy EAC cell Ehrlich ascites carcinoma [ 219 ] Mukonal Murraya koenigii Beclin-1↑ Induce autophagy MDA-MB-231; SK-BR-3 (IC 50 = 7.5 μM) Breast cancer [ 228 ] Evodiamine Evodia rutaecarpa Beclin-1↑ Induce autophagy SGC-7901 Gastric cancer [ 229 ] Bufothionine Toad Bufo bufo gargarizans Cantor JAK2/STAT3↓ Induce autophagy SMMC-7721 Hepatocellular carcinoma [ 233 ] Reduced scytonemin Nostoc commune ROS↑ LC3-II↑ Induce autophagy Jurkat (IC 50 = 1.8 μM) Leukemia [ 239 ] Fascaplysin Fascaplysinopsis sp. ROS, p8↑ …”
Section: Targeting Autophagic Signaling Pathways With Indole Alkaloid...mentioning
confidence: 99%
See 1 more Smart Citation
“…and Pellina sp. p62/SQSTM1, LC3-II↑ Inhibit autophagy AsPC-1 and PANC-1 Pancreatic cancer [ 216 ] Indole-3-carbinol Cruciferous vegetables p62↓ LC3-II↑ Induce autophagy EAC cell Ehrlich ascites carcinoma [ 219 ] Mukonal Murraya koenigii Beclin-1↑ Induce autophagy MDA-MB-231; SK-BR-3 (IC 50 = 7.5 μM) Breast cancer [ 228 ] Evodiamine Evodia rutaecarpa Beclin-1↑ Induce autophagy SGC-7901 Gastric cancer [ 229 ] Bufothionine Toad Bufo bufo gargarizans Cantor JAK2/STAT3↓ Induce autophagy SMMC-7721 Hepatocellular carcinoma [ 233 ] Reduced scytonemin Nostoc commune ROS↑ LC3-II↑ Induce autophagy Jurkat (IC 50 = 1.8 μM) Leukemia [ 239 ] Fascaplysin Fascaplysinopsis sp. ROS, p8↑ …”
Section: Targeting Autophagic Signaling Pathways With Indole Alkaloid...mentioning
confidence: 99%
“…In mukonal-treated breast cancer cells, there was an increase in the expression level of autophagy proteins, Beclin-1, LC3-I, and LC3-II, thus leading to autophagic cell death. Besides, in vivo experiment indicated that mukonal could significantly reduce tumor weight and volume [ 228 ]. Moreover, Beclin-1 was also involved in the evodiamine-induced autophagic death of gastric cancer cells, and its expression level was significantly increased in SGC-7901 cells [ 229 ].…”
Section: Targeting Autophagic Signaling Pathways With Indole Alkaloid...mentioning
confidence: 99%
“…Mukonal (Figure 4 and Table 3; 20, IC 50 : 7.5 µM, MTT assay), an active member of carbazole alkaloids isolated from Murraya koenigii, had the potential to induce antiproliferative effects against MDA-MB-231 and SK-BR-3 cells and no significant toxicity (IC 50 : 110 µM) of mukonal was observed in case of normal MB-157 breast cells. [57,58] 7-Methoxymukonal (21, IC 50 : 82.6 µM, MTT assay), isolated from the root bark of Clausena harmandiana, showed moderate activity against HepG2 cells. [59] The mechanistic studies illustrated that cancer cells.…”
Section: Indolocarbazole Alkaloidsmentioning
confidence: 99%
“…Murraya species is one of the richest sources of carbazole alkaloids [25]. A few carbazole alkaloids such as mukonal, mahanine, and girinimbine isolated from this plant have shown significant anticancer activity, particularly in breast cancer [26][27][28][29]. Mahanimbine (MN) is a carbazole alkaloid and is present in the leaves of this plant (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%